Cash Waqf Nazhir: Efforts to Increase the Role of Islamic Banks in Supporting Cash Waqf - Noviendri Djalil; Luthfi Rantaprasaja; Aan Kurnia (Research of Islamic Economics, 2026)
This study examines the potential of cash waqf as a strategic instrument to support government programs on community empowerment and national economic development. Cash waqf, when aggregated within a formal repository, can serve as a substantial source of business capital; however, its utilization remains suboptimal. Strengthening the role of Islamic banks as Nazhir is expected to optimize this potential by ensuring transparency, accountability, and effective distribution of waqf funds. Using a literature review and descriptive qualitative analysis, this study provides insights for policymakers to accelerate the establishment of a regulatory framework that enables Islamic banks to manage cash waqf. The findings imply that integrating Islamic banks into waqf management not only improves governance but also expands financing access for micro, small, and medium enterprises (MSMEs), thereby enhancing financial inclusion and reducing socio-economic disparities. The originality of this research lies in its emphasis on the institutional role of Islamic banks within the national waqf system, offering a novel paradigm that bridges Islamic social finance with the formal banking sector. This perspective contributes to the optimization of cash waqf as a structured and sustainable instrument for advancing the sharia economy